Pelatihan Melukis Pot Dekorasi Taman Bagi Anak Binaan Pondok Yatim dan Dhuafa - Elda Franzia Jasjfi; Layla Nurina Kartika Iskandar; RA Heryani Wahyuningrum; Erlina Novianti; Edria Putrinda Sofyan; Erin Valencia; Rhomina Hestiningtyas (Abdi Seni, 2025)
Environmental awareness education needs to be carried out continuously starting from childhood. Various ways can be done to increase awareness of the environment, by interacting directly with the environment and increasing the beauty of the environment through artistic activities. The location of the training activities is the Pondok Yatim dan Dhuafa Tomang managed by Yayasan Amal Sholeh Sejahtera, which is inhabited by 10 children aged 5-12 years, located on Jl. Gelong Baru No. 8, Tomang, Grogol Petamburan, West Jakarta. To build environmental awareness, environmental-themed drawing training has been carried out for underprivileged children at Pondok Yatim dan Dhuafa Tomang. In this activity, it was found that children have many interests in drawing activities. For this reason, this program was continued with training in painting pots as garden decorations at Pondok Yatim dan Dhuafa Tomang. The pondok has a front yard area, which contains several green plants but has not been processed by involving the assisted children in cultivating the front yard area of ​​the cottage. The activity of decorating plant pots in your yard is a form of interaction with the surrounding environment and can also improve the aesthetics of the environment so that it is more attractive. The training method is carried out directly by a team consisting of lecturers and students from the Visual Communication Design, Interior Design and Photography study programs. The training material includes insight into the garden environment around your home, tools and media for planting and painting, procedures for painting pots, and creativity in painting garden decoration pots. The results of the training were 10 (ten) individual works of the training participants to paint aesthetic garden decoration pots to be used in the Pondok Yatim dan Dhuafa Tomang environment. Keywords: garden decoration; children creativity; painting pots; environment